PEMAHAMAN KONSEP PESERTA DIDIK DITINJAU DARI GAYA BELAJAR PADA MATERI KINEMATIKA GERAK LURUS - Wafila, Wafila; Syamsu, Syamsu (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aimed to determine the understanding of students' concepts on linear motion in kinematics based on learning styles. This research was a descriptive-qualitative research. 8 respondents who have a high level of conceptual understanding for each learning style involved in this research. Data were collected using reasoned multiple choice test consisting of 10 questions accompanied by a CRI (Certainty Of Response Index) column, a Kolb learning style questionnaire, and followed by interviews. Based on the learning style questionnaire, it is known that 14.81% of students use a divergent learning style, 14.81% with an assimilator learning style, 33.33% use a converger learning style, and students with a dominant learning style, namely the accommodator learning style with a percentage by 37.04%. For conceptual understanding on this topic, the percentage of diverger style, assimilator, and accommodator style were 50%, 47.5% and 26% respectively.